Experiences of sport tourism among multiethnic Malaysian women / Khor Poy Hua and Lim Khong Chiu - Khor, Poy Hua; Lim, Khong Chiu (Research Management Institute (RMI), 2012)
Malaysian women’s practices in leisure vary significantly from those experienced by the general population as they abide by cultural traditions to a greater extent than other. This study explored the leisure barriers and negotiation strategies experienced by multiethnic Malaysian women in sport tourism pursuit. The hierarchical model of leisure constraints developed by Crawford, Jackson, and Godbey (1991) was used as the reference theory. Multistage cluster random sampling with proportional design was used to draw samples and data was gathered from 636 multiethnic Malaysian women of all ages, using a self-administered questionnaire. Although cultural constraint was the main barrier perceived, the majority of multiethnic Malaysian women’s experiences in sport tourism quests were related to interpersonal features. Negotiations were made possible through interpersonal coordination strategies, skill acquisition strategies, financial resource strategies, and time management strategies. This study could possibly guide sport tourism operators in formulating strategies to enhance competitiveness in the multiethnic local and global sport tourism markets.